2020
DOI: 10.1186/s12903-020-01225-0
|View full text |Cite
|
Sign up to set email alerts
|

Status of dental caries and associated factors in Tibetan adults: findings from the fourth China National Oral Health Survey

Abstract: Background Tibet, a region where average elevation is above 3500 m and socio-economic development is relatively lower, was not included in National Oral Health Survey over decades. The cross-sectional study aimed to investigate the status of dental caries and associated factors in Tibetan adults. Methods Participants aged 35–44, 55–64 and 65–74 years were selected. Decayed, missing, and filled tooth (DMFT), decayed and filled root (DF-Root) and root canal index (RCI) were used to evaluate dental caries. Ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
3
7
0
Order By: Relevance
“…National or regional oral health surveys are seen as increasingly important to assess oral health needs, monitor oral health status including disparities among populations and regions and plan intervention programs and policies at national and local levels. 12 Furthermore, understanding gender disparities in oral health might potentially help facilitate strategies toward sustainable oral health. 13 This is because previous epidemiological and clinical studies have revealed a consistent trend in caries development with females having higher prevalence than males.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…National or regional oral health surveys are seen as increasingly important to assess oral health needs, monitor oral health status including disparities among populations and regions and plan intervention programs and policies at national and local levels. 12 Furthermore, understanding gender disparities in oral health might potentially help facilitate strategies toward sustainable oral health. 13 This is because previous epidemiological and clinical studies have revealed a consistent trend in caries development with females having higher prevalence than males.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the paucity of nationwide data, oral health information has been limited in Myanmar, representing a challenge for strategic planning, policymaking and effective services. National or regional oral health surveys are seen as increasingly important to assess oral health needs, monitor oral health status including disparities among populations and regions and plan intervention programs and policies at national and local levels 12 . Furthermore, understanding gender disparities in oral health might potentially help facilitate strategies toward sustainable oral health 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Our study showed that alpha diversity of the oral microbiota decreased with altitude, indicating that a higher prevalence of oral diseases might occur in Tibetans at high altitudes (Guan et al 2020;Hou et al 2014;Wu et al 2020). Some studies have demonstrated that the oral microbiota is consistent with the intestinal microbiota, possibly because most oral bacteria can colonize the intestine (Atarashi et al 2017;Cao 2017;Schmidt et al 2019;Kitamoto et al 2020).…”
Section: Comparison Of Alpha and Beta Diversity Of The Oral Microbiotmentioning
confidence: 50%
“…Publications on the dental status of people aged 45-74 are infrequent, and findings are rarely analyzed by sex. There are several publications in the available literature on the dental condition of middle-aged and elderly men; however, groups of male respondents rarely exceed 200 individuals [15][16][17][18][19]. Su et al [20] evaluated sex differences with regard to oral health and habits in the United States of 4741 subjects (average age was 53.7 years old).…”
Section: Introductionmentioning
confidence: 99%